New species of Cerambycinae from the Neotropical Region, and nomen novum for Anelaphus maculatus Galileo, Martins, and Santos-Silva, 2014 (Elaphidiini) - Galileo, Maria Helena M.; Martins, Ubirajara R.; Santos-Silva, Antonio (Zootaxa, 2015)
Six new species and one new genus are described: Criodion spinosum sp. nov. (Cerambycini), from Bolivia; Eburodacrys wappesi sp. nov. and Eburodacrys skillmani sp. nov. (Eburiini), from Bolivia; Eupempelus rileyorum sp. nov. (Heteropsini) from Panama; Sphalloeme mexicana sp. nov. (Oemini), from Mexico; Wappesoeme camiri sp. nov., new genus (Oemini), from Bolivia. Wappesoeme, Eburodacrys wappesi, E. skillmani, Eupempelus rileyorum, and Criodion spinosum are included in previously published keys. Anelaphus erakyra nomen novum for A. maculatus Galileo et al., 2014 is established.